Five Years Pathological Evaluation of Corneal Regrafts: A Study from Southern Iran - Masoomeh Eghtedari; Mahmood Kamalzadeh; Masoud Yasemi; Hossein Movahedan; Mohammad Javad Ashraf (Journal of Ophthalmology)
Purpose. Corneal regrafts sometimes needed to restore the transparency after graft failure. The aim of the study is five years epidemiologic and histopathological evaluation of corneal regrafts. Methods. In this cross-sectional study, all corneal regrafts during 5 years (2012–2016) were assessed in the Khalili Ophthalmology Center at Shiraz city. Demographic data including age, area of residence, primary disease, type of graft, cause of regraft, interval between primary and subsequent grafts (IPSG), associated eye diseases or surgeries, and systemic diseases were recorded. Also, microscopic findings of corneas were reviewed. Results. Among a total of 1190 corneal grafts, 76 of them (6.38%) were regrafts. The most common type of grafting was penetrating keratoplasty (PK). The shortest IPSG was observed in fungal keratitis. Main causes of graft failure were endothelial dysfunction, infection, immunologic rejection, technical problems, and recurrence of primary disease, respectively. The most common histopathological finding in failed grafts was severe endothelial cell loss (89.8%). Also, more than half and one-third of cases had Descemet membrane changes and stromal ingrowth, respectively. Conclusion. Endothelial cell loss was the major cause of failure in our study. Also, recurrence rate in infective cases, especially fungal keratitis, was very high. Considerable presence of histopathological changes such as doubling of Descemet membrane and retrocorneal fibrous ingrowth need further investigations. Perhaps, modification in techniques of corneal grafting and assessment of donor tissue and recipient bed along with any need for longer medical treatment are the basis for future studies in order to increase graft survival.